2011
DOI: 10.1111/j.1460-9568.2011.07826.x
|View full text |Cite
|
Sign up to set email alerts
|

Nav1.1 dysfunction in genetic epilepsy with febrile seizures-plus or Dravet syndrome

Abstract: Relatively few SCN1A mutations associated with genetic epilepsy with febrile seizures plus (GEFS+) and Dravet syndrome (DS) have been functionally characterized. In contrast to GEFS+, many mutations detected in DS patients are predicted to have complete loss-of-function. However, functional consequences are not immediately apparent for DS missense mutations. Therefore, we performed biophysical analysis of three SCN1A missense mutations (R865G, R946C, and R946H) we detected in six patients with DS. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
4
45
0
Order By: Relevance
“…However, because all of the other mutants were examined using only one substrate, it remains a possibility that some mutations in CPA6 alter the selectivity of the enzyme. Both gain-of-function (31,32) and loss-of-function (33)(34)(35) mutations of other genes have been found to cause epilepsy. We expect that both types of mutations in CPA6 could lead to epilepsy; however, in vitro experiments present difficulties in discriminating between the two, as it is not always clear how these mutations will affect the human brain in vivo (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, because all of the other mutants were examined using only one substrate, it remains a possibility that some mutations in CPA6 alter the selectivity of the enzyme. Both gain-of-function (31,32) and loss-of-function (33)(34)(35) mutations of other genes have been found to cause epilepsy. We expect that both types of mutations in CPA6 could lead to epilepsy; however, in vitro experiments present difficulties in discriminating between the two, as it is not always clear how these mutations will affect the human brain in vivo (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations in VSDs have been reported to cause hypokalemic periodic paralysis (HypoPP) and normokalemic periodic paralysis (NormoPP), cardiac arrhythmias associated with dilated cardiomyopathy, peripheral nerve hyperexcitability, and epilepsy. Most of the mutations related to these channelopathies are located on the S4 segment of the VSDs of the Na v 1.1, Na v 1.2, Na v 1.4, Na v 1.5, Ca v 1.1, and K v 7.4 channels (Gosselin-Badaroudine et al 2012b, 2013Matthews et al 2009;Misra et al 2008;Volkers et al 2011;Wuttke et al 2007). The biophysical characterization of several of these mutations has revealed the presence of an alternative permeation pathway through VSDs, which are usually non-conductive.…”
Section: Introductionmentioning
confidence: 97%
“…Further studies revealed that loss-of-function variants found in DS patients and studied in mouse models induce hyperexcitability and decrease of Na + current in neocortical (Ogiwara et al 2007) and hippocampal (Yu et al 2006) γ-aminobutyric acid (GABA) ergic inhibitory interneurons. Volker and colleagues, on the other hand, performed and described a biophysical analysis of an identified variant, which surprisingly causes DS by overall gain of function (Volkers et al 2011). It should also be mentioned that in some cases missense variants in SCN1A can also be associated with DS (Ohmori et al 2002;Fukuma et al 2004); however, we did not identify possibly pathogenic Clinical significance was determined according to dbSNP database (Sherry et al 2001); N/A, not available.…”
Section: Discussionmentioning
confidence: 88%